Selected stories - Chekhov, Anton Pavlovich, 1860-1904.; Dunnigan, Ann. (New York : Signet Classic, 2003)
520 Selected stories by Anton Pavlovich Chekhov. 600 10 Chekhov, Anton Pavlovich,|d1860-1904|vTranslations into English.
The confession -- The understood -- At sea--a sailor's story -- A nincompoop -- Surgery -- Ninochka--a love story -- A cure for drinking -- The jailer jailed -- The dance pianist -- The milksop -- Marriage in ten or fifteen years -- In Spring -- Agafya -- The kiss -- The father -- In exile -- Three years -- The house with the mansard--an artist's story -- Peasants -- The darling.
Includes bibliographical references.
Keywords: Chekhov, Anton Pavlovich, -- 1860-1904 -- Translations into English; 650 0 Russian fiction|vTranslations into English; Short stories, Russian